Intraoperative safety of low pressure pneumoperitoneum cholecystectomy: a comparative study - Mahajan, Salil; Shankar, Manu; Garg, Vinod K.; Gupta, Vijender; Sorout, Jaya (International Surgery Journal, 2017)
Background: With the establishment of laparoscopic cholecystectomy as gold standard for management of cholelithiasis, the current stress is on increasing patient safety. Hence, this study was undertaken to compare the effect of low pressure pneumoperitoneum (LPP <10mm Hg) versus high pressure pneumoperitoneum (HPP >14mm Hg) in a prospective randomized manner on intraoperative safety, assessing the working space and safety by seeing contact of parietal peritoneum to underlying viscera during secondary port insertion. Methods: 120 patients undergoing laparoscopic cholecystectomy were randomized into the LPP (<10mm Hg) group (n=60) and the HPP (>14mm Hg) group (n=60) prospectively. Available working space assessed directly, safety by contact of parietal peritoneum to underlying viscera during secondary port insertion and operative difficulty assessed by visualization, dissection and grasping, total duration of surgery; intra-operative gas consumption, and bile spillage were assessed. Results: There was no significant difference in terms of available working space, operative duration, consumption of carbon dioxide, surgeon’s operative difficulty and intraoperative bile spillage. Out of 180 secondary ports inserted, there was evident contact of 20 (11.1%) secondary ports in high pressure groups and 14 (7.7%) secondary ports in low pressure group, which is suggestive of adequate exposure and working space available for surgery at both pressures. Conclusions: Low-pressure cholecystectomy did not compromise intraoperative safety and should be the standard of care in day care surgery.